2003
DOI: 10.3354/dao054001
|View full text |Cite
|
Sign up to set email alerts
|

A model of spatially evolving herpesvirus epidemics causing mass mortality in Australian pilchard Sardinops sagax

Abstract: In 1995 mass mortality of pilchards Sardinops sagax occurred along > 5000 km of Australian coast; similar events occurred in 1998/99. This mortality was closely associated with a herpesvirus. The pilchard is an important food source for larger animals and supports commercial fisheries. Both epidemics originated in South Australian waters and spread as waves with velocities of 10 to 40 km d -1. Velocity was constant for a single wave, but varied between the epidemics and between the east-and west-bound waves in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…In several months it spread thousands of kilometres bidirectionally along the Australian coastline, and then to New Zealand . A similar event occurred a few years later in 1998/1999 (Murray et al, 2003). Affected pilchards showed progressive gill inflammation followed by epithelial hypertrophy and hyperplasia .…”
Section: Pilchard Herpesvirusmentioning
confidence: 86%
“…In several months it spread thousands of kilometres bidirectionally along the Australian coastline, and then to New Zealand . A similar event occurred a few years later in 1998/1999 (Murray et al, 2003). Affected pilchards showed progressive gill inflammation followed by epithelial hypertrophy and hyperplasia .…”
Section: Pilchard Herpesvirusmentioning
confidence: 86%
“…Pilchards surviving the epizootic had lesions consistent with infection by PHV. This suggested that they had survived, rather than avoided, infection (Murray et al 2003). These survivors showed few signs of disease 8 d after the front had passed .…”
Section: Introductionmentioning
confidence: 99%
“…Models have been proposed to explain how the virus spread so quickly. The most recent research proposed that the schooling patterns of pilchards, involving contact within and also between schools, allowed the rapid spread of the disease from a point source (Murray et al 2003). During the disease outbreak, affected pilchards were observed to exhibit signs of stress only a few minutes before dying , allowing infected and uninfected fish to school together (Murray et al 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concentrations of the virus in sardine from these fisheries may be low, especially in healthy, wild-caught fish (Arkush et al 2006). Despite these large volumes of imported and likely VHSVinfected bait, there has been no indication of the spread of the virus among wild fish, salmonids or other pen-raised fish populations in Australia, although mass mortalities by herpesvirus of Australian pilchard Sardinops sagax have been reported (Murray et al 2003). However, a key difference between the Chilean and Australian marine environments is water temperature: southern Chile is much cooler and thus potentially more conducive to VHSV infection compared to South Australia.…”
Section: Likelihood Of a Vhsv Introduction To Chilementioning
confidence: 99%